Implementasi Pembelajaran Direct Learning Pada Pembelajaran Agama Hindu Di SMAN 1 Kahayan Hulu Utara Kabupaten Gunung Mas - Kismita Kismita; Mitro Mitro; I Putu Widyanto (Institut Agama Hindu Negeri Tampung Penyang Palangkaraya, 2024)
In the achievement process, learning outcomes are greatly influenced by various factors. One of the main factors that is very influential in the success of learning is the presence of the teacher. At SMAN 1 Kahayan Hulu Utara, Gunung Mas Regency, it was found that students were less active during the learning process and paid less attention to the material presented by the teacher, most students were busy alone with their classmates. This is because the learning methods used by teachers in delivering material have not been able to actively involve students. So students become lazy to ask questions and express their opinions, there is a lack of student understanding of the concepts used. One of the factors identified is the limited ability of teachers to deliver material and the lack of involving students in the learning process. In learning Hinduism, the method currently used is the direct learning model. The research method used is qualitative research, and the technique for determining informants uses purposive. Data obtained by observation, interviews, and smartphones as instruments in this research. The data analysis technique goes through four stages, namely: data collection, data reduction, data presentation, and drawing conclusions. The results of this research were studied using humanistic theory and motivation theory. The results of the study show that: (1) The implementation of direct learning in Hindu learning subjects at SMAN 1 Kahayan Hulu Utara, Gunung Mas Regency, is carried out by teachers by first carrying out learning activities, such as presenting materials, presenting lessons to attract students' attention, providing structured exercises by strengthening the correct response to students, and motivating and evoking students' work results. Teachers also provide independent exercises to help students develop their abilities.: (2) Obstacles in the implementation of direct learning include low student absorption, lack of participation, and lack of discipline, so that the implementation of learning is not optimal because students are passive: (3) Teachers' efforts in overcoming these obstacles are by designing more specific and relavanted learning strategies so that the learning process can be well accepted by student.